(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
An ecological catastrophe should be understood as the transition of a system from one stable state to another. For example, an increase in the average temperature of the Earth can lead to the melting of polar ice, desertification of soils, the extinction of certain species of flora and fauna, and perhaps even the death of mankind. Nevertheless, the Earth as an element of the solar system is likely to remain as stable as before. Environmental catastrophes can have different levels - from local (death of a forest, drying up of the sea, etc.) to global ones (on the scale of the Earth, the Solar System, the Galaxy, and even the Universe).